Validity of Phet Simulation Assisted Poe2we Learning Model on Ideal Gas Materials - Muhamad Aqil Ridho; Agung Suci Dian Sari (SAGA: Journal of Technology and Information System, 2023)
The purpose of this study was to describe the validity of the POE2WE model physics learning device assisted by PhET simulation to improve students' critical thinking skills. The learning tools described include the syllabus, lesson plans, LKPD, textbooks and pre-test post-test questions. The research was conducted in class XI SMA Negeri 2 Pasuruan on ideal gases. Descriptive-quantitative data analysis technique by describing and describing the assessment in percentage of agreement. The results showed that the percentage of syllabus validity was 95.75% in the very valid category, the percentage of RPP validity was 96.75% in the very valid category, the LKPD validity was 96.50% in the very valid category, the validity of textbooks was 94.25% with the category is very valid, and the validity of the pre-test post-test is 95.50% with a very valid category. Based on the results of the analysis of the data obtained, it can be stated that the learning device developed is feasible to use with very valid criteria.